KONTRIBUSI PENERIMAAN USAHATANI KACANG PANJANG DI LAHAN SAWAH TADAH HUJAN PADA BERBAGAI POLA TANAM (Kasus di Kecamatan Pondok Kelapa, Kabupaten Bengkulu Tengah) - Wawan Eka Putra; Sudarmansyah Sudarmansyah; Andi Ishak (AGRITEPA: Jurnal Ilmu dan Teknologi Pertanian, 2020)
Long bean is an important crop for vegetable farmers on rainfed ricefield in Pondok Kelapa District, Bengkulu Tengah Regency because its cultivated in various cropping patterns. This study aims to analyze the contribution of long bean farming revenue in various vegetable cropping patterns. The study was conducted from May to August 2019 through a census of 50 vegetable farmers in the villages of Srikuncoro and Pekik Nyaring, Pondok Kelapa District. Data collected in the form of production costs and sale of the yields. The contribution of long bean farming is analyzed descriptively by calculating the revenue percentage in each cropping pattern. The results showed that there were six vegetable planting patterns practiced by farmers in Pondok Kelapa District, namely: (1) cucumber - pariah - long bean, (2) cucumber - gambas - long bean, (3) cucumber - long bean - long bean, (4) long bean - pariah - long bean, (5) long bean - gambas - long bean, and (6) long bean - long bean – pulled kale – pulled kale. Farmers always plant long bean in all of the cropping patterns. The biggest farming benefit is obtained from cropping pattern 1 which is Rp. 120,244,000/hectare with an R/C ratio of 1.95, while the smallest profit on a cropping pattern of 6 with an R/C ratio of 1.55. The planting pattern of cucumbers - long beans - long beans nominally gives the largest farm receipts from all cropping patterns namely Rp. 120,000,000/hectare, meanwhile, the long-bean-long-bean-spinach-pull-out cropping pattern is a cropping pattern which contributes the largest revenue from long-bean farming to 64.00%. Keywords : long bean, planting pattern, contribution, revenue.